In Vitro Evaluation of Different Surface Treatments on Osseointegration of Dental Implants - Rajnee Yadav; Bharani K. Bhattu; Bhavini B. Solanki; Palak A. Pandya; Hiroj Bagde; Manish Kumar; Mahesh Ghadage; HM Khuthija Khanam (Journal of Pharmacy and Bioallied Sciences)
Background: Osseointegration is a critical factor determining the success of dental implants. Various surface treatments are applied to enhance the integration of implants with the surrounding bone tissue. Materials and Methods: Standardized dental implants were divided into four groups based on the surface treatment applied: Group A (machined surface), Group B (sandblasted and acid-etched), Group C (plasma-sprayed hydroxyapatite coating), and Group D (titanium oxide nano-coating). Implants were embedded in bovine bone blocks and subjected to biomechanical testing after a simulated healing period of 8 weeks under controlled conditions. Parameters assessed included bone-implant contact (BIC) percentage and pull-out strength (N). Results: Group A exhibited the lowest BIC percentage (45%) and pull-out strength (150 N). Group B demonstrated a significant improvement with a BIC of 65% and pull-out strength of 210 N. Group C achieved a BIC of 75% and pull-out strength of 250 N. Group D showed the highest values, with a BIC of 85% and pull-out strength of 300 N. Statistical analysis revealed that Groups C and D performed significantly better (P < 0.05) compared to Groups A and B. Conclusion: Surface treatments significantly influence the osseointegration of dental implants. Titanium oxide nano-coating and plasma-sprayed hydroxyapatite coatings demonstrated superior results, suggesting their potential as preferred surface modification techniques for enhancing implant success. Further clinical studies are recommended to validate these findings.